Development and Evaluation of a Horizontal Air-Staged Biomassto-Heat Energy Converter - Chong, Kok Hing (University Malaysia Sarawak, UNIMAS, 2015)
Biomass fuel in Malaysia contributes 16% of the energy consumption, of which 51% is from palm oil biomass waste and 27% from wood waste. The drying industry in Malaysia can utilize these biomass wastes as fuel instead of fossil fuel, which emits higher air pollutants. In the biomass combustion field, there is little or no research on the effects of the air velocity ratio on a horizontal combustor’s temperature profile, flue gas composition and combustion efficiency; therefore, the investigation presented in this thesis is aimed at improving the understanding of the biomass combustion in this area. In this research project, an experimental study of an air-staged horizontal combustor with quantities of oil palm kernel shell (OPKS) and wood chips was conducted and carried out in two phases: Phase I – Development (Design and Fabrication) of Biomass-to-Heat (B2H) Converter and Phase II – Emission Evaluation of B2H Converter. A quantification of the thermal properties and moisture contents of the selected biomass was carried out, in addition to emission evaluation of the B2H converter. The influence of the air velocity ratio (AVR) on the temperature profile, flue gas composition and combustion efficiency from OPKS and wood chips was determined, using a Testo 350XL flue gas analyser. It was observed that by increasing the AVR, the mean temperature of the pyrolysis chamber would be increased; however, it would result in a decrease in the mean temperature in the exhaust. With respect to air emissions, CO, H2, NOx and SO2 levels were inversely proportional to increase in the AVR and the combustion efficiency of the B2H converter was also inversely proportional to increase in AVR. The experimental results confirmed that the horizontal air-staged B2H converter allows cleaner and more efficient combustion with OPKS and wood chips as feedstock. Moreover, a biomass combustion model that can be validated with the experimental data generated in this work can be developed.